SIFAT FISIK VULKANISAT KARET DENGAN BAHAN PENGISI VARIASI TANAH LIAT DI BERBAGAI LAPISAN AREA TAMBANG PT. BUKIT ASAM (PERSERO) TBK. - Hasan, Abu; Dewi, Erwana; Purnamasari, Indah; Irawan, Dewanda; A.S, Putu Yoga (Politeknik Negeri Sriwijaya, 2019)
This study aims to study the physical characteristics of vulcanized rubber using various clay fillers from layers in the PT. Bukit Asam (Persero) Tbk .. This research was conducted 6 formulas (1,2,3,4,5,6), each variation of clay type INT A2-B1, OBA1, Lower C, INT A1-A2, INT B2-C, INT B1-B2. Then with the same variation carried out the addition of chemicals in the form of JHS-69 and PEG 4000 in each of the 6 formulas as much as 1 phr. The natural rubber used is RSS-1 then rubber is modified and vulcanized along with other process materials in the open mill. Based on the results of the study it has been analyzed that rubber compound number 4 using JH-S69 is better than other rubber compounds, which have a tensile strength value of 17.2 Mpa, elongation at break of 670%, modulus of 300% 4 Mpa, and tear strength 33 kN / m. Whereas the best rubber compound using PEG 4000 is compound number 2 which has a tensile strength value of 16.6 Mpa, elongation at break of 690%, modulus of 300% 2.4 Mpa, and tear strength 28.8 kN / m. From the results of the analysis of the physical properties, the two compounds meet the SNI 0778:2009 standards to be used as shoe soles products.